Teman (Tablet Effervescent Manggis) Pengembangan Dan Pengolahan Ekstrak Kulit Manggis Menjadi Effervescent Sebagai Suplement Kesehatan ditinjau dari Value Propotion Canvas dan Lean Canvas - Kartika Sari; Tantri Yanuar Rahmat Syah; Edi Hamdi; Agus Munandar (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
Indonesia is one of the strategic markets for the world's health and food supplement industry. And along with the increase in people's purchasing power, the consumption of health supplements is also becoming a trend. And currently, mangosteen fruit extract is processed and marketed in conventional forms, ranging from syrups to capsules and another inefficient packaging. The business model for making mangosteen fruit extract into an effervescent tablet product is currently not available on the market, so producing it can be a business opportunity. The system development method used in this research uses the lean canvas method as business analysis. By applying lean canvas, it can make it easier for makers to carry out the validation process because they can see the overall business model, reducing the risks of doing business. This is done because the product offered is new